(untitled) (Comunicação & Inovação, 2024)
The article explores the development of an indicator system for a Creative Industry (CI) observatory at the University of Porto. The research, of an exploratory nature, describes and proposes a conceptual framework for analyzing indicators in CI. It highlights the importance of interdisciplinarity by integrating economic and infocommunicational perspectives. The complexity of defining and classifying economic activities in this sector is addressed. The article also presents a proposal in development for the observatory and suggests the use of descriptive, predictive, and prescriptive models in future stages.